Efficient cascade C-N coupling reactions catalyzed by a recyclable MoOx/ Nb2O5 nanomaterial for valuable N-heterocycles synthesis - Singh, Nittan; Kalbande, Pavan Narayan; Umbarkar, Shubhangi; Sudarsanam, Putla (Molecular Catalysis, 2022)
The efficient cascade synthesis of pharmaceutically valuable N-heterocycles at solvent-free conditions was achieved using a robust, recyclable MoOx/Nb2O5 nanocatalyst. The results of catalyst screening revealed that the MoOx/Nb2O5 nanorods, calcined at 500 degrees C (MoNb5), exhibit excellent catalytic activity in the oxidative coupling of benzylamine with 96.5% conversion and >99.6% selectivity to the desirable imine product. The uniform dispersion of Mo-oxide nanoparticles (average particle size: 5.2 +/- 0.5 nm) on shape-controlled Nb2O5 nanorods (width: 5.3 +/- 0.5 nm and length: 23-38 nm) in MoNb5 catalyst led to improved structural and acid properties, beneficial for the cascade C-N bond construction. The shape-controlled MoNb5 catalyst showed versatile activity in various cascade C-N coupling reactions to obtain 2-phenylbenzimidazole, 2-phenyl-quinaxoline, and 2-phenyl-2,3-dihydroquinazolin-4(1H)-one with good to excellent yields at solvent-free con-ditions. The optimum ratio of Lewis/Bronsted acid sites, the unique structure of Nb2O5 nanorods, and the strong MoO3-Nb2O5 interaction are the key reasons for the higher activity of MoNb5 catalyst. The efficient reusability of MoNb5 catalyst, its remarkable activity in diverse N-heterocycles synthesis, and efficient gram-scale synthesis emphasize its practical application for the cascade C-N coupling reactions under benign conditions.
Keywords: Acid sites optimization; Cascade C-N bond formation; Diverse nitrogenous chemicals; Heterogeneous nanosized catalyst; MoO3-Nb2O5 interaction; Nb2O5 nanorods